IMPLEMENTASI DEKLARASI RIO: ANALISIS PENGATURAN KRITERIA DAN STANDAR PROGRAM CSR OLEH MULTINATIONAL ENTERPRISES (MNC) BERBASIS KONSEP SUSTAINABLE - deli bunga saravistha; I Made Adi Widnyana (Jurusan Hukum Fakultas Dharma Duta Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
The rule of law is obliged to uphold the enforcement and protection of human rights (HAM), related to the survival of mankind, so this issue is very important. Indonesia in its capacity as a subject of international law has made an agreement on the Declaration of Human Rights, this is evidenced by the stipulation of the 1999 Human Rights Law. Optimization steps related to efforts to uphold and protect human rights are continued by focusing attention on environmental issues (LH) and sustainability through sustainable development. Development Goals (SDGs), specifically regarding environmental issues, agreed on the Rio Declaration which established 27 principles regarding the protection and management of the environment which are very closely related to human rights. One of the efforts in this regard is to look at the actors that contribute to pollution and the biggest pollution, namely the industrial sector, especially corporations. The solution to this is the establishment of corporate responsibility or CSR. However, these programs are often done for nothing. Fulfill the formal requirements regulated in positive law. This is what is interesting to study, research and analyze further through two issues, namely related to the nature of CSR implementation and also arrangements for setting certain CSR criteria or standards for companies in certain fields in Indonesia in the context of fulfilling human rights to enjoy a clean and healthy environment and evaluating on the constraints of implementing CSR in the context of implementing its arrangements for MNCs.